"The sufferings of Christ are abundant in us" (2 Corinthians 1:5) : a narrative-dynamics investigation of Paul's sufferings in 2 Corinthians /: a narrative-dynamics investigation of Paul's sufferings in 2 Corinthians. (©2009) - Unknown
No abstract available